2002
DOI: 10.2174/1381612023394430
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Imaging of HSVtk Gene Therapy

Abstract: The evolution of molecular biology has enabled the exploration of novel sophisticated gene-directed treating modalities for cancer. Suicide gene therapy - i.e. transfection of a so-called suicide gene that sensitizes target cells towards a prodrug - may offer an attractive approach to treat malignant tumors. For the development of effective clinical suicide gene therapy protocols, a non-invasive method to assay the extent, the kinetics and the spatial distribution of transgene expression is essential. This wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The lipophilic PCV and FHBG ligands reveal hepatobiliary and renal excretion pathways, sometimes making it harder to interpret reporter gene expression in the abdominal/pelvic areas [36]. The use of [ 124 I]FIAU can be limited with deiodination in vivo, constraints in 124 I availability, and a relatively long half-life (t 1/2 = 4.2 days) limiting serial imaging [37]. Recently, Alauddin [25] reported biodistribution and microPET imaging studies of [ 18 F]FEAU in HT-29 (tk+ and tkj) tumor-bearing mice and demonstrated a lower magnitude of tumor uptake but comparable uptake ratio tk+/tkj with FMAU.…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic PCV and FHBG ligands reveal hepatobiliary and renal excretion pathways, sometimes making it harder to interpret reporter gene expression in the abdominal/pelvic areas [36]. The use of [ 124 I]FIAU can be limited with deiodination in vivo, constraints in 124 I availability, and a relatively long half-life (t 1/2 = 4.2 days) limiting serial imaging [37]. Recently, Alauddin [25] reported biodistribution and microPET imaging studies of [ 18 F]FEAU in HT-29 (tk+ and tkj) tumor-bearing mice and demonstrated a lower magnitude of tumor uptake but comparable uptake ratio tk+/tkj with FMAU.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular imaging of reporters on particular therapeutic genes could be critical in optimizing gene therapy. The aim of these approaches is to quantitatively image reporter gene expression, and from this to infer levels, location, and duration of therapeutic gene expression (Gambhir et al 2000b;MacLaren et al 2000;Weissleder et al 2000;Wunderbaldinger et al 2000;Allport and Weissleder 2001;Berger and Gambhir 2001;Nichol and Kim 2001;Vries et al 2002). There are several strategies to achieve linkage of expression of the therapeutic transgene and the imaging reporter gene (Ray et al 2001;Sundaresan and Gambhir 2002).…”
Section: Applications Of Reporter Gene Imaging: Imaging Of Gene Theramentioning
confidence: 99%
“…As more probes accumulate within the cells, signal strength increases and can be detected by PET [109]. The herpes simplex virus thymidine kinase (HSV1-tk) gene has been the most extensively studied enzyme-based reporter gene for PET applications, and several radiolabeled acyclo-guanosine and pyrimidine nucleoside analogues have been investigated as reporter probes for imaging of HSV1-tk [110]. Pyrimidine derivatives for PET have used various isotopes as a radiolabel (Fig.…”
Section: Enzyme-based Reporter Systemmentioning
confidence: 99%